HEV study protocol : design of a cluster-randomised, blinded trial to assess the safety, immunogenicity and effectiveness of the hepatitis E vaccine HEV 239 (Hecolin) in women of childbearing age in rural Bangladesh. Issue 1 (19th January 2020) - Zaman, K; Dudman, Susanne; Stene-Johansen, Kathrine; Qadri, Firdausi; Yunus, Md; Sandbu, Synne; Gurley, Emily S; Overbo, Joakim; Julin, Cathinka Halle; Dembinski, Jennifer Lynn; Nahar, Quamrun; Rahman, Anisur; et al.
Abstract : Introduction: Hepatitis E virus (HEV) is a leading cause of acute viral hepatitis in the developing world and is a public health problem, in particular among pregnant women, where it may lead to severe or fatal complications. A recombinant HEV vaccine, 239 (Hecolin; Xiamen Innovax Biotech, Xiamen, China), is licensed in China, but WHO calls for further studies to evaluate the safety and immunogenicity of this vaccine in vulnerable populations, and to evaluate protection in pregnancy. We are therefore conducting a phase IV trial to assess the effectiveness, safety and immunogenicity of the HEV 239 vaccine when given in women of childbearing age in rural Bangladesh, where HEV infection is endemic. Methods and analysis: Enrolment of a target of approximately 20 000 non-pregnant women, aged 16–39 years, started on 2 October 2017 in Matlab, Bangladesh. Sixty-seven villages were randomised by village at a 1:1 ratio to receive either the HEV vaccine or the control vaccine (hepatitis B vaccine). A 3-dose vaccination series at 0, 1 and 6 months is ongoing, and women are followed up for 24 months. The primary outcome is confirmed HEV disease among pregnant women. After vaccination, participants are requested to report information about clinical hepatitis symptoms. Participants who become pregnant are visited at their homes every 2 weeks to collect information about pregnancy outcome and to screen for clinical hepatitis. All suspected hepatitis cases undergo laboratory testing for diagnostic evaluation. The incidence of confirmed HEV disease among pregnant and non-pregnant women will be compared between the HEV vaccinated and control groups, safety and immunogenicity of the vaccine will also be evaluated. Ethics and dissemination: The protocol was reviewed and approved by the International Centre for Diarrhoeal Disease Research, Bangladesh Research Review Committee and Ethical Review Committee, and the Directorate General of Drug Administration in Bangladesh, and by the Regional Ethics Committee in Norway. This article is based on the protocol version 2.2 dated 29 June 2017. We will present the results through peer-reviewed publications and at international conferences. Trial registration number: The trial is registered at clinicaltrials.gov with the registry name "Effectiveness Trial to Evaluate Protection of Pregnant Women by Hepatitis E Vaccine in Bangladesh" and the identifier NCT02759991 .